Perceptions of plastic pollution among inland fishery stakeholders in a subtropical reservoir - Florence M. Murungweni; Manamela S. Mokata; Lubabalo Mofu; Jeffrey Lebepe; Samuel N. Motitsoe; Thendo Mutshekwa (PLoS ONE, 2026)
Plastic pollution is becoming a serious problem in freshwater ecosystems, impacting the livelihoods of people who rely on inland fisheries. Although plastic waste is widely discussed around the world, limited research has explored how local fishery stakeholders perceive pollution, particularly in Southern Africa. As such, using semi-structured interviews, the current study assessed the awareness, concerns, and solution perspectives of three different stakeholder groups, i.e., commercial fishers (CF), recreational fishers (RF), and fishmongers (FM) around Nandoni Dam, a subtropical reservoir in Limpopo Province, South Africa. Thirty participants, i.e., 10 per stakeholder, were interviewed, and our results showed that 96.7% of all stakeholders were aware of plastic pollution, yet 86.7% had limited understanding of microplastics. Perceptions of the impacts of plastic pollution varied across groups, with visitors (CF = 60%; RF = 60%; FM = 66.7%) and local residents (CF = 20%; RF = 20%; FM = 11.1%) being linked as a source of plastic pollution around Nandoni Dam. Willingness to participate in reducing plastic pollution was high across stakeholders (CF = 90%; RF = 90%; FM = 70%), with the majority emphasising the need for local municipal involvement and community engagement during clean-up activities and awareness initiatives. These findings highlight the need for targeted environmental education, and enhanced community-municipal collaboration to improve awareness and support collective action against plastic pollution in inland fisheries. Strengthening these actions could promote sustainable fisheries management, protect inland waters, and improve the well-being of the people who rely on these waters for food, income, and daily activities.